Aung San Suu Kyi a biography - Bengtsson, Jesper 1968- (Amaryllis, 2012)
This book weaves together the personal and political life of Nobel laureate and democratic icon Aung San Suu Kyi, who has been the face of the peaceful movement for freedom in Burma for decades now. This book is a result of a number of interviews that the author had with Aung San, and examines her life from up-close and presents her views and thoughts on many issues in her own words - like the years she spent in India and the deep influence that Mahatma Gandhi had on her life.